2000
DOI: 10.1105/tpc.12.5.739
|View full text |Cite
|
Sign up to set email alerts
|

Protein Recycling from the Golgi Apparatus to the Endoplasmic Reticulum in Plants and Its Minor Contribution to Calreticulin Retention

Abstract: Using pulse-chase experiments combined with immunoprecipitation and N-glycan structural analysis, we showed that the retrieval mechanism of proteins from post-endoplasmic reticulum (post-ER) compartments is active in plant cells at levels similar to those described previously for animal cells. For instance, recycling from the Golgi apparatus back to the ER is sufficient to block the secretion of as much as 90% of an extracellular protein such as the cell wall invertase fused with an HDEL C-terminal tetrapeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 76 publications
6
69
1
7
Order By: Relevance
“…Other studies suggested that all the glycans present were of the OMT class, indicating more efficient ER retrieval (Pagny et al, 2000;Sriraman et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Other studies suggested that all the glycans present were of the OMT class, indicating more efficient ER retrieval (Pagny et al, 2000;Sriraman et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Glycosylation processing in the ER is conserved amongst almost all species and restricted to OM (Man 5–9 GlcNAc 2 )-type glycans, whereas the Golgi-generated glycans are highly diverse [14]. In plants, the addition of KDEL at the C-terminal end of a protein is sufficient for the protein to be retained in the ER [15], [16]. mAb P s with KDEL fused to their heavy chain (HC) and light chain (LC) therefore contain exclusively non-immunogenic, OM type glycans with stable ER accumulation [17].…”
Section: Introductionmentioning
confidence: 99%
“…These include: chaperone proteins that ensure properprotein folding (3034); the presence of endoplasmic reticulum (ER) retention signals which need to be cleaved before protein can be transported out of ER (35, 36); post-translational modification such as glycosylation and phosphorylation which ensure proper folding and structure stability (37); and/or protein-specific accessory proteins in the ER before surface transport(36, 38, 39). In B-cells, the requirement for immunoglobulin M (IgM) surface protein expression has been well-defined (36, 40, 41).…”
Section: Discussionmentioning
confidence: 99%